Executive Committee Minutes 2012-03-15 - Academic Senate:::::::::
Revision to the MS Family Nursing Practitioner approved for the Senate consent calendar. Revision to the Theater Arts Program approved for the Senate consent calendar. Request for routing paths for policies from APC. Student Fee Referendum Code as Information Item to the Senate approved.